2007
DOI: 10.1097/01.aog.0000279448.62221.a8
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Thromboembolism in Women Taking Ethinylestradiol/Drospirenone and Other Oral Contraceptives

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
105
1
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(110 citation statements)
references
References 16 publications
0
105
1
4
Order By: Relevance
“…1 Among users of combined oral contraceptives, the incidence of venous thromboembolism for matched controls was comparable to that of users in the general population (7-11/10 000 person-years), 17,19 while the incidence among women with PCOS was doubled. Similarly, among women not using oral contraceptives, the incidence of venous thromboembolism among those without PCOS was close to previously reported baseline rates, 17 while those with PCOS had increased risk.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…1 Among users of combined oral contraceptives, the incidence of venous thromboembolism for matched controls was comparable to that of users in the general population (7-11/10 000 person-years), 17,19 while the incidence among women with PCOS was doubled. Similarly, among women not using oral contraceptives, the incidence of venous thromboembolism among those without PCOS was close to previously reported baseline rates, 17 while those with PCOS had increased risk.…”
Section: Discussionmentioning
confidence: 90%
“…20 Previous studies have found that combined oral contraceptives are effective for the reduction of androgen levels and hirsutism in women with PCOS; these studies have mainly focused on drospirenone, desogestrel and cyproterone acetate. 8,9,19 These studies were small in size and not powered to assess thrombotic events.…”
Section: Discussionmentioning
confidence: 99%
“…[16,17,18,19]. Drei davon sind retrospektive Auswertungen von Krankengeschichten [16,18,19], eine ist eine prospektive multizentrische Studie [17] Ob das Risiko eher relativ tief und vergleichbar mit demjenigen der KOK der 2. Generation oder allenfalls etwas höher wie bei den KOK der 3.…”
Section: Epidemiologische Studienunclassified
“…9. 2009, Swissmedic a reçu au total dix annonces d'embolies pulmonaires ayant entraîné un décès mis en relation avec des contraceptifs hormonaux,c'est-à-dire avec des COC antiandrogéniques ( contraceptifs hormonaux [16,17,18,19]. Trois études sont des analyses rétrospectives de dossiers médicaux [16,18,19], une est une étude prospective multicentrique [17] dans laquelle les patientes donnaient initialment elles-mêmesdes informations sur les diagnostics et sur les expositions en répondant à un questionnaire.…”
Section: Annonces Spontanées En Suisseunclassified
“…Les auteurs de l'étude européenne EURAS [17] et ceux de l'étude américaine INGENIX [16] sont tous parvenus à la conclusion que les COC-D n'entraînent pas de risque supérieur aux autres COC. Ces deux études ont inclus, outre des cas idiopathiques, égale-ment des cas présentant des facteurs de risque directs, tels qu'un trauma récent ou une opération chirurgicale.…”
Section: Annonces Spontanées En Suisseunclassified